The impact of weather patterns and related transport processes on aviation's contribution to ozone and methane concentrations from NO x emissions - S. Rosanka; C. Frömming; V. Grewe (Atmospheric Chemistry and Physics, 2020)
Aviation-attributed climate impact depends on a combination of composition changes in trace gases due to emissions of carbon dioxide ( CO 2 ) and non- CO 2 species. Nitrogen oxides ( NO x = NO + NO 2 ) emissions induce an increase in ozone ( O 3 ) and a depletion of methane ( CH 4 ), leading to a climate warming and a cooling, respectively. In contrast to CO 2 , non- CO 2 contributions to the atmospheric composition are short lived and are thus characterised by a high spatial and temporal variability. In this study, we investigate the influence of weather patterns and their related transport processes on composition changes caused by aviation-attributed NO x emissions. This is achieved by using the atmospheric chemistry model EMAC (ECHAM/MESSy). Representative weather situations were simulated in which unit NO x emissions are initialised in specific air parcels at typical flight altitudes over the North Atlantic flight sector. By explicitly calculating contributions to the O 3 and CH 4 concentrations induced by these emissions, interactions between trace gas composition changes and weather conditions along the trajectory of each air parcel are investigated. Previous studies showed a clear correlation between the prevailing weather situation at the time when the NO x emission occurs and the climate impact of the NO x emission. Here, we show that the aviation NO x contribution to ozone is characterised by the time and magnitude of its maximum and demonstrate that a high O 3 maximum is only possible if the maximum occurs early after the emission. Early maxima occur only if the air parcel, in which the NO x emission occurred, is transported to lower altitudes, where the chemical activity is high. This downward transport is caused by subsidence in high-pressure systems. A high ozone magnitude only occurs if the air parcel is transported downward into a region in which the ozone production is efficient. This efficiency is limited by atmospheric NO x and HO x concentrations during summer and winter, respectively. We ...